Reversible Dilation of the Superior Ophthalmic Vein in Intubated Patients - Nabavizadeh, S.A.; Sundararajan, S.H.; Schmitt, J.E.; Loevner, L.A. (American Journal of Neuroradiology, 2018)
BACKGROUND AND PURPOSE: Superior ophthalmic vein enlargement has typically been associated with increased intracranial or orbital pressure. This study evaluates the incidence of superior ophthalmic vein enlargement in intubated patients without pre-existing intracranial or intraorbital pathologies.MATERIALS AND METHODS: Two cohorts (patients with trauma and epilepsy patients undergoing stereotactic intracranial lead placement) who underwent CT while intubated and shortly following extubation and a cohort of 30 outpatients with a history of headache and normal head CT findings (healthy controls) were included. The superior ophthalmic vein diameter was measured on all scans.RESULTS: Seventy patients intubated for trauma and 45 patients with intraoperative CT were included (n = 115). While intubated, 66% of the total sample had at least unilateral superior ophthalmic vein dilation of >2.5 mm and 48% had bilateral dilation. Fifty-seven percent of patients with trauma and 84% of intraoperative patients with dilated superior ophthalmic veins showed reversal of mean superior ophthalmic vein dilation to <2.5 mm on postextubation CT. The mean superior ophthalmic vein diameter decreased an average of 1.2 mm following extubation. Changes in superior ophthalmic vein diameter between intubated and extubated states were statistically significant (P < .001). Differences between the control group and the extubated subjects were not statistically significant (P = .21).CONCLUSIONS: Bilateral dilation of the superior ophthalmic vein is common in intubated patients and usually reverses following extubation. In the appropriate clinical setting, this knowledge will prevent misinterpretation of prominent superior ophthalmic veins as automatically indicative of an underlying pathology.SOVsuperior ophthalmic vein